Geophysical prospecting of copper-nickel deposits in Beishan rift zone, Xinjiang - Jing-zi He; Zheng-guo Fan; Sheng-qing Xiong; Teng-fei Ge; Xu-zhao Huang; Si-xun Wang (China Geology, 2021)
ABSTRACT: The Beishan rift zone in Xinjiang Uygur Autonomous Region was formed due to strong activities of faults on the basement of the Tarim continental crust. Despite the fact that many geological research results of the rift zone have been achieved, only a few studies have been conducted on its regional geophysical characteristics. In this paper, the gravity and magnetic anomalies of the rift zone were highlighted through specific data processing of 1:50000 high-precision aeromagnetic data and gravity data with a grid spacing of 2 km × 2 km. Based on this, the geophysical evidence for the scope and internal structures of the Beishan rift zone was obtained for the first time. The distinct characteristics of magnetic and gravity fields in the areas to the north and south of the Beishan rift zone reveal that deep faults exist between the Beishan rift zone and the geological units on the southern and northern sides. Furthermore, the faults on the two areas contain the bidirectional thrusts and have flower-shaped structures according to the characteristics of the magnetic and gravity fields. The Beishan rift zone can be divided into two tectonomagmatic zones, namely the Zhongposhan-Bijiashan-Cihai-Baishanliang zone (the northern zone) and the Bayiquan-Qixin-Baishan zone (the southern zone). The northern zone can be further subdivided into three comet-shaped anomaly groups (tectonomagmatic areas), while the southern zone can be further subdivided into two tectonomagmatic areas. According to the characteristics of aeromagnetic anomalies and gravity field, 19 mafic-ultramafic complexes were delineated. The known Pobei, Hongshishan, and Qixin complexes are all located within the inferred complexes, with estimates of total explored resources of Ni, Cu, and Au of 3×106 t, 10×103 t and 10 t, respectively. The prospecting of high-grade copper-nickel deposits should focus on the periphery and deep parts of the known and inferred mafic-ultramafic complexes. Among them, the peripheral strata of the complexes specifically have great prospecting potential of large-scale high-grade copper-nickel deposits of magma injection type. Finally, this paper analyzed the application effects of the rapid airborne-ground-drilling synergetic exploration method in the prospecting of copper-nickel deposits in Qixin, Beishan, Xinjiang, which will provide references for further exploration of copper-nickel deposits in Beishan area, Xinjiang.©2021 China Geology Editorial Office.